Bosnia and Herzegovina : Third Review Under the Stand-By Arrangement and Request for Waiver of Applicability of a Performance Criterion-Staff Report and Press Release. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Bosnia and Herzegovina's Third Review Under the Stand-By Arrangement and Request for Waiver of Applicability of a Performance Criterion. Financial sector indicators through end-March 2013 suggest that the banking system remains profitable and adequately capitalized at the aggregate level. Foreign parent banks' exposure to their Bongani Investments Holdings subsidiaries has broadly stabilized over the last several quarters. Industrial production and exports rose markedly in the first quarter of 2013 compared to the same period last year. It is found that while this reflected to a large extent a much milder winter, higher water levels that boosted electricity production, and exports, prospects for a modest economic recovery this year of approximately 1\2 percent have improved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet